Thorough QTc Study of a Single Supratherapeutic Dose of Relebactam in Healthy Participants. Issue 4 (25th March 2020) - Boundy, Keith; Liu, Yang; Bhagunde, Pratik; O'Reilly, Terry E.; Colon‐Gonzalez, Francheska; Friedman, Evan J.; Lala, Mallika; Rhee, Elizabeth G.; Rizk, Matthew L.
Abstract: The effects of supratherapeutic doses of intravenous (IV) relebactam on duration of ventricular depolarization and subsequent repolarization were assessed in a thorough QT/corrected QT study. This was a single‐dose, double‐blind (relebactam only), randomized, placebo‐ and positive‐controlled, 3‐period, balanced crossover study in healthy participants. Participants received in randomized order, and separated by a washout (≥4 days), a single dose of IV relebactam 1150 mg, oral moxifloxacin 400 mg (open‐label positive control), and IV placebo. Least squares mean and 2‐sided 90% confidence interval for change from baseline in population‐derived corrected QT intervals for relebactam, moxifloxacin, and placebo were estimated for 24 hours. The upper limit of the 90% confidence interval of all least squares mean population‐derived corrected QT treatment differences from placebo was not >10 milliseconds at any time point for 24 hours. Corrected QT assay sensitivity was confirmed with moxifloxacin treatment. Analysis of electrocardiogram parameters resulted in no additional cardiac safety concerns. Overall, a supratherapeutic dose of relebactam yielded no cardiac safety events; the 1150‐mg supratherapeutic dose (4.6‐fold above the 250‐mg therapeutic dose) was not associated with QT prolongation or other abnormal cardiodynamic parameters. This study lends additional support to relebactam's use as a β‐lactamase inhibitor in antimicrobial therapy.